2018
DOI: 10.2503/hortj.okd-085
|View full text |Cite
|
Sign up to set email alerts
|

Preventive Effect and Mode of Action of Repetitive Hot Water Spraying against Powdery Mildew in Strawberry

Abstract: This study aimed to investigate the preventive effect of periodic hot water spraying against powdery mildew in strawberry as an alternative to chemical application as a protection method. Young upper leaves of 'Sachinoka' were dipped in hot water at 50°C for 20 s. Conidia of powdery mildew were inoculated 24 h after the treatment. The occurrence and growth rates of powdery mildew were apparently lower on leaves dipped in hot water than on those left untreated. Thus, resistance against powdery mildew was though… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 9 publications
0
9
0
Order By: Relevance
“…However, no major yield loss was observed. Sato et al (2018) reported that weekly HWS did not affect June-bearing strawberry yield throughout the cultivation period. Despite its relatively higher powdery mildew incidence, the yield under the F treatment was the same as that under the F+HWS treatment.…”
Section: Strawberry Yieldmentioning
confidence: 94%
See 3 more Smart Citations
“…However, no major yield loss was observed. Sato et al (2018) reported that weekly HWS did not affect June-bearing strawberry yield throughout the cultivation period. Despite its relatively higher powdery mildew incidence, the yield under the F treatment was the same as that under the F+HWS treatment.…”
Section: Strawberry Yieldmentioning
confidence: 94%
“…Figure 3 shows that the DI under the F+HWS treatment after August 2016 did not rapidly decrease after infection. Sato et al (2018) reported that HSIR was only prophylactic and not therapeutic. Moreover, the field-level duration of induced resistance was <1 week in the June-bearing varieties.…”
Section: Efficacy Of Hot Water Spray Against Powdery Mildew Incidencementioning
confidence: 99%
See 2 more Smart Citations
“…Additionally, chemical-resistant powdery mildew is expanding in this area. Recently, heat shock treatment using hot water was shown to be a potential alternative to chemical protection against powdery mildew (Ogawara et al, 2012;Sato et al, 2018). This treatment was adapted to long-term cultivation ( Fig.…”
Section: Development Of a Methods For Long-term Cultivationmentioning
confidence: 99%